The Criterion Validity and Between-Day Reliability of the Perch for Measuring Barbell Velocity During Commonly Used Resistance Training Exercises. Issue 4 (4th April 2023) - Weakley, Jonathon; Munteanu, Gabriella; Cowley, Nicholas; Johnston, Rich; Morrison, Matthew; Gardiner, Carissa; Pérez-Castilla, Alejandro; García-Ramos, Amador
Abstract: Weakley, J, Munteanu, G, Cowley, N, Johnston, R, Morrison, M, Gardiner, C, Pérez-Castilla, A, and García-Ramos, A. The criterion validity and between-day reliability of the Perch for measuring barbell velocity during commonly used resistance training exercises. J Strength Cond Res 37(4): 787–792, 2023—This study aimed to assess the criterion validity and between-day reliability (accounting for technological and biological variability) of mean and peak concentric velocity from the Perch measurement system. On 2 testing occasions, 16 subjects completed repetitions at 20, 40, 60, 80, 90, and 100% of 1-repetition maximum in the free-weight barbell back squat and bench press. To assess criterion validity, values from the Perch and a 3-dimensional motion capture system (criterion) were compared. Technological variability was assessed by determining whether the differences between the Perch and criterion for each load were comparable for both testing sessions, whereas between-day reliability with both technological and biological variability was calculated from Perch values across days. Generalized estimating equations were used to calculate R 2 and root mean square error, whereas Bland-Altman plots assessed magnitude of difference between measures. To support monitoring of athletes over time, standard error of measurement and minimum detectable changes (MDC) were calculated. There was excellent agreement between the Perch and criterion device, with mean velocity in both exercises demonstrating a mean bias ranging from −0.01 to 0.01 m·s −1 . For peak velocity, Perch underestimated velocity compared with the criterion ranging from −0.08 to −0.12 m·s −1 for the back squat and −0.01 to −0.02 m·s −1 for the bench press. Technological variability between-days were all less than the MDC. These findings demonstrate that the Perch provides valid and reliable mean and peak concentric velocity outputs across a range of velocities. Therefore, practitioners can confidently implement this device for the monitoring and prescription of resistance training.